BPP-enhanced core–shell structured multilayer hyperbolic metamaterial composite as SERS substrate for ultrasensitive molecular detection - Wei, Zhuofan; Shan, Xiaomu; Shi, Jian; Xu, Yuanze; Wang, Sen; Jiang, Shouzhen (Mikrochimica acta (1966), 2025)
A surface-enhanced Raman scattering (SERS) composite substrate based on the synergy between Au@ZIF-8 nanoparticles (NPs) and multilayer Au/Al 2 O 3 thin films (MLFs) was designed to achieve electromagnetic field enhancement by coupling localized surface plasmon resonance (LSPR) with bulk plasmon polariton (BPP). Surface plasmon polaritons (SPPs) in MLFs can couple to form BPP, which significantly enhance the localized electric field intensity within the Au@ZIF-8 (zeolitic imidazolate framework-8) nanogaps. Moreover, the electric field amplification increases progressively with the number of film layers. Within the Au@ZIF-8 core–shell structure, the ZIF-8 serves as a shell to control particle spacing (thereby preventing agglomeration) and concentrate probe molecules within electromagnetic field hotspots. The experimental results demonstrate detection limits of 8.6 × 10 −12 M for rhodamine 6G (R6G) and 1.5 × 10 −9 M for Crystal Violet (CV), representing a significant improvement compared with conventional SERS substrates. This study provides new insights into the synergistic mechanisms of SPP with LSPR, and demonstrates the potential applications of composite Raman substrates in ultrasensitive molecular detection. Graphical Abstract